Evaluasi Pembelajaran Pendidikan Kesetaraan Paket B dan C - Hilmansyah, Muhamad; Yuliani, Nadya Amalia; Tresnasih, Tasya; Mardiani, Syalsha Farabilla (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The aim of this research is to find out how the learning evaluation system works and understand the role of packages B and C in achieving learning objectives at PKBM Al-Mujahidin Tasikmalaya City. This research method uses qualitative descriptive research with data collection techniques, namely conducting interviews with the chairman and one of the tutors from PKBM Al-Mujahidin Tasikmalaya City. In this research, the research subjects were residents studying Package B and Package C at PKBM Al-Mujahidin, Tasikmalaya City, and the object of research was the evaluation of package B and Package C learning at PKBM Al-Mujahidin, Tasikmalaya City. The results of this research conclude that learning evaluation at PKBM Al-Mujahidin is a process of determining the results that have been achieved by several planned activities to support the achievement of objectives and the evaluation system at PKBM Al-Mujahidin is adjusted to the regulations of the education service.